2015
DOI: 10.1155/2015/391065
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic Activity and Antiatherosclerotic Effect of Polysaccharide ofPolygonatum sibiricumin Rabbit Model and Related Cellular Mechanisms

Abstract: Objective. To evaluate the hypolipidemic activity and antiatherosclerotic effect of polysaccharide of Polygonatum sibiricum (PPGS), which is a kind of Chinese herbal medicine using the rhizome part of the whole herb. Materials and Methods. Thirty rabbits were divided into normal control group, model control group, and PPGS subgroups of 0.8, 1.6, and 3.2 mL/kg/day under random selection. In atherosclerosis model, the effects of PPGS on diverse blood lipids, foam cells number, and aortic morphology were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…Some studies confirmed that the hypolipidemic activity of PSP was mainly due to modulation of TC, low-density lipoprotein (LDL-C), and lipoprotein (Lp (a)) in an atherosclerosis model. [ 16 ] PSP significantly reduced the intimal foam cells number compared to the control group. According to a study in endothelial cells (ECs), PSP not only affected EC proliferation, but also protected ECs from injury and apoptosis induced by H 2 O 2 and lipopolysaccharide (LPS).…”
Section: Pharmacological Applicationsmentioning
confidence: 94%
See 1 more Smart Citation
“…Some studies confirmed that the hypolipidemic activity of PSP was mainly due to modulation of TC, low-density lipoprotein (LDL-C), and lipoprotein (Lp (a)) in an atherosclerosis model. [ 16 ] PSP significantly reduced the intimal foam cells number compared to the control group. According to a study in endothelial cells (ECs), PSP not only affected EC proliferation, but also protected ECs from injury and apoptosis induced by H 2 O 2 and lipopolysaccharide (LPS).…”
Section: Pharmacological Applicationsmentioning
confidence: 94%
“…PSP were found to be the major contributors to the sweet taste of PS which makes the food more readily accepted [ 14 ]. At present, PSP are widely used in TCM therapy for cardiovascular diseases and other diseases [ 15 , 16 , 17 , 18 , 19 , 20 ]. In conclusions, PSP play an important role in PS, which is commonly used in people’s lives.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 80 male Sprague Dawley (SD) rats (200 AE 20 g, two months old) were purchased from SPF (Beijing) Experimental Animal Technology Co. Ltd. All rats were housed under controlled conditions (22)(23)(24) C, 12:12 h light/dark cycle) and provided with food and water ad libitum. All experiments were approved by the laboratory animals' ethical committee of Taishan Medical University and followed national guidelines for the care and use of animals.…”
Section: Animalmentioning
confidence: 99%
“…Polysaccharides isolated from P. sibiricum (PSPs) are major contributors to sweet taste and have many important biological functions [ 3 ]. The results of animal and cell experiments have shown that these compounds can promote the proliferation and enhance the viability of mesenchymal stem cells in bones [ 4 ], help prevent Alzheimer’s disease [ 5 ] and osteoporosis [ 6 ], serve as hypolipidemics and antiatherosclerotics [ 7 ], and improve immunologic functions [ 8 ]. Their polysaccharide structures and composition are closely related to their biological functions.…”
Section: Introductionmentioning
confidence: 99%